Evaluation of vestibular functions in children with vertigo attacks - TÜRKDOĞAN, DİLŞAD (BMJ PUBLISHING GROUP, 2003)
Aim: To examine vestibular system functions in children with episodic vertigo attacks. Methods: Thirty four children (20 males) aged 4-18 years with paroxysmal dizziness and/or vertigo attacks were evaluated. A medical history for vestibular symptoms and migraine was taken. Vestibular and auditory functions were assessed. Results: Chronic headache attacks consistent with migraine were reported in 12 children and motion sickness was reported in 30. Family history in first degree relatives was positive for migraine in 29 children and for episodic vertigo in 22. Electronystagmography and videonystagmography showed two types of nystagmus: spontaneous vestibular nystagmus (41%) and benign paroxysmal positional nystagmus (BPPN) (59%). The first type of nystagmus was assessed as a sign of vestibulopathy and the patients with BPPN were diagnosed as having benign paroxysmal positional vertigo (BPPV). Audiometric examination in four cases revealed bilateral sensory neural hearing loss in low frequencies. Pure tone averages in 30 cases were within normal ranges; however low frequencies in 28 of them were approximately 10 dB lower than high frequencies. Unilateral caloric responses diminished in eight children. Conclusions: Peripheral vestibular problems in childhood present in a wide spectrum, which varies from a short episode of dizziness to a typical vestibular attack with fluctuating sensory neural hearing loss or episodes of BPPV. A considerable number of these vestibular problems might be related to the migraine syndrome.
Keywords: BENIGN PAROXYSMAL VERTIGO; POSITIONAL VERTIGO; CHILDHOOD